The promise - Weisgarber, Ann (Skyhorse Publishing, 2014)
1900. Young pianist Catherine Wainwright flees the fashionable town of Dayton, Ohio in the wake of a terrible scandal. Heartbroken and facing destitution, she finds herself striking up correspondence with a childhood admirer, the recently widowed Oscar Williams. In desperation she agrees to marry him. But when Catherine travels to Oscar's farm on Galveston Island, Texas - a thousand miles from home - she finds she is little prepared for the life that awaits her.